INTEGRATING MODEL FOR SUSTAINABLE DEVELOPMENT - С.К. Рамазанов; И.В. Заблодська; Д.В. Заблодська (Економіка та право, 2024)
The article presents the integration model of sustainable development as a family of models for creation of integrated information systems of ecological economic and socio-humanitarian management of different socio-organizational systems and especially economic objects of technogenic character for ensuring the sustainable and viable development. The problem of sustainable development for the "hexagon" of main assets (capitals), supporting the vital activity of socio-ecological-economic systems is considered and defined: the concept of sustainable development, the system of sustainable development global dimensions, and the level of sustainable development.